Rancang Bangun Aplikasi Penilaian Kerja Praktek (KP) Berbasis Android Program Studi Teknik Informatika Universitas Muhammadiyah Purwokerto - Harjono Harjono; Lahan Adi Purwanto (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2015)
Job Training is a compulsory curriculum implemented by each student in Informatics Engineering Program, Engineering Department, Muhammadiyah University of Purwokerto. Assessment of Job Training is a process that must be done. The assessment process cannot be done if there are no examinees Job Training, so the process starts from the assessment exam registration process of Job Training. This process should be done with a practical and efficient, so as to speed up services for students. By using the tools of Visual Studio 2010, SQL Server 2008, Eclipse Indigo, and the C# and Java programming language, in this research resulted in the application assessment of Job Training along with the application for registration. The Application examination registration of Job Training as well as its application administrator in the form of web-based applications, whereas Job Training assessment applications in the form of Android-based applications. This application is expected to improve academic performance in Informatics Engineering Program Engineering Department, University of Muhammadiyah Purwokerto